HUMAN AND ANIMAL DYNAMICS IN PETER PAN BY J.M. BARRIE: A LINGUISTIC PERSPECTIVE FROM THE EDWARDIAN ERA - Sahira Shofa, Ghaitsa; Puji Haryanti, Rahayu (Esteem Journal of English Education Study Programme, 2025)
This article discusses the representation of the relationship between humans and animals in J.M. Barrie's Peter Pan through an ecocritical approach. The main focus of this study is the character of a dog named Nana who acts as a caregiver for the children of the Darling family in the socio-cultural setting of the Edwardian era. By using close reading method and contextual-historical approach, this research reveals how Nana is not only portrayed as a pet, but also as a loving, responsible, and emotionally intelligent human being. However, Nana's position remains in a subordinate structure that reflects human domination over animals. This analysis shows that Nana's representation reflects Edwardian society's ambivalence towards animals: between affection and exploitation, between emotional closeness and denial of equality. Through an ecocritical approach, this article emphasizes the importance of rereading classic literary works as an effort to build ecological awareness and ethics towards non-human living beings, especially in the context of children's literature and environmental education.